Does health literacy affect the uptake of annual physical check-ups?: Results from the 2017 US health information national trends survey - Hee Yun Lee; Sooyoung Kim; Jessica Neese; Mi Hwa Lee (BMC, 2021)
Abstract Background Little is known about how health literacy is linked to physical check-ups. This study aimed to examine the levels of physical check-ups (self-reported check-ups within the last year) by age group (those aged 18-59 years and those aged = ≥ 60 years) and the role of health literacy regarding physical check-ups in the United States. Methods Data for the study were obtained from the 2017 Health Information National Trends Survey. The original sample included 3,285 respondents, but only 3,146 surveys were used for this study. Andersen's Behavioral Model of Health Services Use guided this study, and a binomial logistic regression model was conducted using Stata 12.0 software package. Results While 82.0 % of the older group had an annual check-up, 67.3 % of the younger group had one. Both groups had similar ratios for health literacy-related item reporting. Study results show that annual check-up was positively associated with confidence in getting health information, having health insurance, and having a primary doctor for both age groups. However, getting a regular check-up was negatively associated with frustration while searching for information among the younger group. In comparison, it was positively associated with difficulty understanding information for the older group. Conclusions To increase annual physical check-ups, health literacy-related interventions should be developed and address the barriers most associated with health check-ups. One way of addressing this barrier is to improve communication from healthcare professionals to consumers through the use of easy-to-understand explanations appropriate for the consumer.